THE PSYCHOLINGUISTIC PROBLEMS OF SPEECH PRODUCTION (INTERNATIONAL SCIENTIFIC E-CONFERENCE " INNOVATIVE TRENDS IN SCIENCE, PRACTICE AND EDUCATION" – Ankara, Turkey, 2024)
Regular and irregular words have long served as metaphors for the lawabiding and the quirky. Psychology textbooks point to children’s errors like breaked and goed as evidence that we are a pattern-loving, exception-hating species, explaining everything from why children have trouble learning simple laws of physics to why adults make errors when using computers or diagnosing diseases. In 1984 George Orwell has the state banning irregular verbs as a sign of its determination to crush the human spirit; in 1989 the writer of a personal ad in the New York Review of Books asked, “Are you an irregular verb?” as a sign of her determination to exalt it.